Effects of PPARγ agonists on the expression of leptin and vascular endothelial growth factor in breast cancer cells12. Issue 6 (25th February 2013) - Terrasi, Marianna; Bazan, Viviana; Caruso, Stefano; Insalaco, Lavinia; Amodeo, Valeria; Fanale, Daniele; Corsini, Lidia Rita; Contaldo, Clara; Mercanti, Anna; Fiorio, Elena; Lo Re, Giuseppe; Cicero, Giuseppe; et al.
Abstract The obesity hormone leptin has been implicated in breast cancer development. Breast cancer cells express the leptin receptor and are able to synthesize leptin in response to obesity‐related stimuli. Furthermore, leptin is a positive regulator of vascular endothelial growth factor (VEGF) and high levels of both proteins are associated with worse prognosis in breast cancer patients. Peroxisome proliferator‐activated receptor γ (PPARγ) ligands are therapeutic agents used in patient with Type 2 diabetes and obesity which have recently been studied for their potential anti‐tumor effect. Here, we studied if these compounds, ciglitazone and GW1929, can affect the expression of leptin and VEGF in breast cancer cells. In MDA‐MB‐231 and MCF‐7 breast cancer cells, treatment with submolar concentrations of ciglitazone and GW1929 elevated the expression of leptin and VEGF mRNA and protein, and increased cell viability and migration. These effects coincided with increased recruitment of PPARγ to the proximal leptin promoter and decreased association of a transcriptional factor Sp1 with this DNA region. J. Cell. Physiol. 228: 1368–1374, 2013. © 2012 Wiley Periodicals, Inc.